2003
DOI: 10.1029/2002je002002
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of Martian dust devils

Abstract: [1] Large eddy simulations of vertical convective vortices and dust devils in the Martian convective boundary layer are presented, employing a version of the Mars MM5 mesoscale model, adapted to use periodic boundary conditions and run at resolutions of 10 to 100 m. The effects of background horizontal wind speed and shear on dust devil development are studied in four simulations, each extending over the daytime portion of one Martian day. The general vorticity development in all cases is similar, with roughly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
106
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 31 publications
12
106
0
Order By: Relevance
“…The dust devils seen at the front of the storm ( Figure 7b) indicate with their computed speeds as well the speed of the dust storm if they are propelled by the storm. This is supported by the simulations by Toigo et al (2003), in which dust devils developed both in the 'highest wind speed' case and in the 'no background wind' case.…”
Section: [Figure 7]supporting
confidence: 67%
“…The dust devils seen at the front of the storm ( Figure 7b) indicate with their computed speeds as well the speed of the dust storm if they are propelled by the storm. This is supported by the simulations by Toigo et al (2003), in which dust devils developed both in the 'highest wind speed' case and in the 'no background wind' case.…”
Section: [Figure 7]supporting
confidence: 67%
“…The last phenomenon was the focus of the Toigo et al (2003) LES study which showed similarities between the modelled vortices and the observed Martian dust devils. These preliminary results were recently confirmed by other studies (Richardson et al, 2007;Sorbjan, 2007;Spiga and Forget, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The formation and evolution of dust storms is a multiphysical process involving dust particle thermal and kinetic energy evolution, dust grain contact electrification and charge separation [Toigo et al, 2003;Farrell et al, 2003]. Initially, surface air molecules and dust grains absorbing heat from sunlight generate pressure and temperature gradients on the surfaces that form vertical wind or local vortices, and dust grains are lifted from the ground.…”
Section: Introductionmentioning
confidence: 99%